2013
DOI: 10.1016/j.atherosclerosis.2013.03.036
|View full text |Cite
|
Sign up to set email alerts
|

Cigarette-smoke-induced atherogenic lipid profiles in plasma and vascular tissue of apolipoprotein E-deficient mice are attenuated by smoking cessation

Abstract: Tobacco smoke exerts perturbations on lipid metabolism and arterial cell function that accelerate atherosclerosis. Lipidomics has emerged as a key technology in helping to elucidate the lipid-related mechanisms of atherosclerosis. In this study, we investigated the effects of smoking cessation on plaque development and aortic arch content of various lipid molecular classes and species. Apolipoprotein E-deficient mice were exposed to fresh air (sham) or to mainstream cigarette smoke (CS) for 6 months, or to CS … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
52
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 50 publications
(61 citation statements)
references
References 27 publications
6
52
1
Order By: Relevance
“…S1P receptor is expressed by ECs and it binds its ligand S1P, a bioactive lipid with numerous functions in the immune and cardiovascular systems. Using a lipidomics approach, we have previously shown that CS exposure increases, whereas cessation decreases, the levels of S1P in plasma of ApoE -/- mice [5,22]. Furthermore, CD36 is a glycoprotein expressed in various vascular and circulatory cell types including monocytes, macrophages, platelets, ECs and adipocytes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…S1P receptor is expressed by ECs and it binds its ligand S1P, a bioactive lipid with numerous functions in the immune and cardiovascular systems. Using a lipidomics approach, we have previously shown that CS exposure increases, whereas cessation decreases, the levels of S1P in plasma of ApoE -/- mice [5,22]. Furthermore, CD36 is a glycoprotein expressed in various vascular and circulatory cell types including monocytes, macrophages, platelets, ECs and adipocytes.…”
Section: Discussionmentioning
confidence: 99%
“…We used the V-IPN network to assess the degree of biological mechanistic coverage from four different sets of transcriptomics profiling data derived from multiple atherosclerotic-relevant contexts including human endothelial cells (ECs) in culture, coronary arteries from coronary artery disease (CAD) patients and aortas from ApoE -/- mice. The systemic inflammatory status of ApoE -/- mice, a well-established model of atherosclerosis [21], makes this strain an ideal model in which to study comorbidities associated to cigarette smoking [22]. Our results indicate that the V-IPN captures the key biological mechanisms that underlie the progression of vascular disease in various cellular and tissue contexts and allows for a comprehensive interrogation of transcriptomics datasets related to atherogenesis and cross-species translatability.…”
Section: Introductionmentioning
confidence: 86%
“…In mouse models exposure to mainstream cigarette smoke led to perturbations of lipid metabolism, arterial endothelial cell function and the development of atherosclerotic lesions (Boue et al, 2012). Cessation of smoke exposure led to decelerated plaque progression and decreased accumulation of pro-atherogenic lipids (Lietz et al, 2013). …”
Section: Risk Factors: Concordance Of Mouse and Human Studiesmentioning
confidence: 99%
“…There is evidence among nondiabetic individuals that potential weight gain after stopping smoking has no impact on the expected reduction of CVDR . In apolipoprotein E‐deficient mice, cessation of exposure to cigarette smoke led to lower levels of proatherogenic lipid species in plasma and vessel walls . Additionally, plasma levels of endothelial progenitor cells, which are usually low in smokers, tend to recover their normal range after smoking cessation .…”
Section: Scientific Evidence In Favour Of Smoking Cessation Strategiementioning
confidence: 99%